Strategi Pembangunan Ekonomi Melalui Peningkatan Skala Bisnis Internasional Di Indonesia - Chavid Moyo Jaladri; Ayu Rachmawaty (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
The aim of this research is to increase economic development by increasing the scale of international business in Indonesia. This research was conducted using qualitative methods, using the liberal research method. A country’s economy can be said to be balanced if it has developed industrial capacity and strength, which are supported by strong economic activity, and the success of a country’s economic development can generally be measured and described by its economic growth. Some of the benefits of international business include: (1) bringing in large amounts of foreign exchange, especially for exporters and producers; (2) an increase in the export side will increase production capacity and production volume, which will result in the availability of new job opportunities; (3) the transfer of goods will occur, which will be followed by an influx of capital into the country; and (4) the transfer of technology from abroad to within the country. Considering the importance of international business for a country’s economic development, in this era of globalization, international business has become a necessity for every nation that wants to progress, especially in the economic sector.